Are highly educated partners really more gender egalitarian? A couple-level analysis of social class differentials in attitudes and behaviors - Liat Raz-Yurovich; Barbara S. Okun (Demographic Research)
BACKGROUND: Research suggests that, following major changes in women’s roles in developed societies, gender relations within heterosexual partnerships are entering a second stage, during which men’s roles are the main source of change. Some scholars suggest that changes in gender roles occur differentially across social classes, as reflected in variation across educational groups. OBJECTIVE: We ask how variation in the educational level of both partners is related to: (1) gender role attitudes and housework contributions of each partner; and (2) consensus between partners on egalitarian gender role attitudes, and gaps between partners in housework hours. METHODS: Analyzing British Household Panel Survey and Understanding Society data on currently married, heterosexual partnerships in the United Kingdom (1992–2018) from a couple-level perspective, we compare across four educational types defined by whether partners have a tertiary-level degree. RESULTS: We find that (1) it is not the male partner’s but rather the female partner’s tertiary education that is a key factor in understanding variation in partners’ gender role attitudes and housework hours, as well as couple-level consensus on gender egalitarian attitudes and between-partner differences in housework hours; and (2) gender gaps in housework hours between partners are smallest among couples in which women are highly educated, primarily because highly educated women do substantially fewer hours than less educated women rather than because their partners do substantially more hours. CONTRIBUTION: Our results highlight that women’s class status, as measured by their education (as distinct from their partner’s), is related to meaningful variation within the household in terms of partners’ values and day-to-day experiences of chores.